Analisa Unjuk Kerja Software Defined Radio (SDR) dengan Teknik Quadrature Amplitude Modulation (QAM) - Putri Hapsari, Jenny; Ismail, Munaf (Infotekmesin, 2021)
The development of wireless communication technology require technology (software and hardware) that can keep up with changing standards. SDR platform is a software-based wireless technology that can keep up with technological developments without changing hardware. WARP is one of SDR platforms developed by American Rice University. This research to determine the performance of the SDR with the QAM technique. The performance system can be seen from BER for different distance between transmitter and receiver and different level QAM. The research was carried in two enviroment (indoor and outdoor) with LOS propagation. The results show that the value of BER 4-QAM in the two enviroment is the smallest than another levels. Thevalue of BER 4-QAM at indoor is 0.0023 and outdoors is 0 for a distance of 6 meters, so the performance of outdoor is better than indoor. SDR performance can be improved using QAM techniques.